PTU-042 Acute upper gastrointestinal bleeding in patients with a glasgow-blatchford score of ≤2 can be safely managed using an ambulatory pathway. (17th June 2017) - Penman, D; Conley, T; Molugu, C; Bassi, A; McLindon, J; Chandy, R; Dobson, J; Fox, M; Priestley, S; Theis, V; McClements, D
Abstract : Introduction: Acute upper GI bleeding (AUGIB) presents with a spectrum of severity. Current NICE guidance recommends risk-stratifying patients using the Glasgow-Blatchford score (GBS) and considering early discharge for patients with a pre-endoscopy Blatchford score of 0 1 . STHK Teaching Hospitals has developed an ambulatory pathway to manage low-risk (GBS ≤2) patients with suspected AUGIB. Patients are commenced on the pathway by a Medical StR, then discharged home with a pre-arranged endoscopy (OGD) and a post-OGD medical review. Our aim was to assess the safety of this strategy. Method: Data between May 2016 and Jan 2017 was retrospectively collected from e-case notes. A standard audit tool was used and included GBS, endoscopy findings, readmission, re-bleeding, transfusion, surgery and death. Local audit data was used to estimate total bed days saved. Results: 68 patients (M:F 34:34) were referred via the Low Risk GI Bleed Ambulatory Pathway. The mean age was 42, range 18–79. Median time to OGD was 1 day, range 0–10. 2 patients elected to defer their endoscopy by 10 days for non-clinical reasons. All patients were discharged after post-OGD medical review. 26 had a normal OGD, 6 had peptic ulcer disease. 5 patients had a delay in the decision to ambulate, mean stay 1.2 days. 1 patient re-presented after 3 months with a suspected AUGIB, GBS was 1 and repeat OGD revealed oesophagitis. 6 patients were inappropriately referred and had GBS>2. No patients had stigmata of recent or active bleeding, none required endotherapy or surgery and no patients died. 1 patient recieved a blood transfusion. Conclusion: Our data shows that patients with GBS ≤2 can potentially be managed safely with an ambulatory pathway and this supports previously published findings 2, 3 . Using local audit data, median and mean length of stay for patients with GBS ≤2 is 2 and 3 days respectively. Between May 2016 and Jan 2017 we estimate to have saved 138–204 bed days. At an estimated cost of £400 per day, this equates to a saving of £55, 200–81, 600 4 . References: . National Institute for Health and Care Excellence, June 2012. Acute upper gastrointestinal bleeding in over 16s : Management [CG141]. London: NICE. . Stewart RF, Murphy RFE, Church NI. "An ambulatory care protocol for managing low-risk patients with non-variceal upper GI bleeding". Society of Acute Medicine Conference, Manchester, England, 30th Dec 2012. . Stanley AJ, et al. Outpatient management of patients with low-risk upper-gastrointestinal haemorrhage: multicentre validation and prospective evaluation. The Lancet, vol 373, No. 9657, p42–47, 3rd Jan 2009. . https://data.gov.uk/data-request/nhs-hospital-stay. Department of Health. Data.gov.uk. NHS Hospital Stay, 24/08/2015.Accessed:17/02/17. Disclosure of Interest: None Declared